The ‘Dutch Case’ and Its Civilizational Dimensions: Situating the Transition Debate to Capitalism - Todorov, Pavlin (Research Papers, 2021)
The Netherlands is considered to be an exemplary case of study of the transition to capitalism. Most studies, however, lack a comprehensive interpretation synthesizing the different aspects and providing a summarized idea of this complex situation. The perception and pursuit of the civilization perspective outlined by M. Weber and F. Braudel, enables the identification of the basic dimensions of early capitalism in the Netherlands. The debate on the transition to capitalism is used as a methodology and interpretative forum for approximation of the views of both scientists and their further development through the prism of contemporary views. The general picture of the epoch of the 17th century outlines the idea that the country has not been completely transformed into capitalist but the process had already started. Certain cultural, economic and political preconditions and factors had contributed to its development whilst it was dependent on their combination both in internal and European and global context. It was found that to a lesser degree the role of the socio-cultural dimensions of capitalism is outlined, which may be based on the factual situation as well as on its incomplete interpretation in the different studies. The pluralistic explanation of the transition to capitalism renders it possible to clarify this assumption and use it in subsequent studies.
Keywords: The Netherlands; Civilization; Dimensions of civilization; Transition to capitalism; Early capitalism; Spirit of capitalism; World-economy; Weber; Braudel; Europe